Mr. Jack is a maniac! - Gutman, Dan; Paillot, Jim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
"A. J. and the Ella Mentry School gang learn some unusual self-defense moves from a wacky teacher who thinks he's an action hero"--
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction; Teachers -- Juvenile fiction; Self-defense -- Juvenile fiction; Humorous stories